Integrated treatment and energy recovery from palm oil mill effluent using laccase-producing microalgae in a microbial fuel cell system - Kongthong, Alisa; Yooyen, Thanapon; Chaijak, Pimprapa (Journal of Degraded and Mining Lands Management, 2025)
The treatment of palm oil mill effluent (POME) remains a significant environmental challenge due to its high organic load, complex pigmentation, and dark color. This study aimed to develop a sustainable low-input approach for POME treatment and bioelectricity generation using a photosynthetic microbial fuel cell (PMFC) under the environmental conditions. The heterotrophic green microalgae Choricystis parasitica SW-03 and the photosynthetic bacterial consortium have been used for pigment degradation and electricity generation. The degraded metabolites were determined using gas chromatography-mass spectrophotometry (GC-MS). The results showed the maximal open circuit voltage (OCV) of 0.702±0.02 V. Maximum current and power densities reached 19.20?±?2.40?mA/m3 and 2.81?±?0.61?mW/m3, respectively. The co-culture also demonstrated strong bioremediation performance. GC-MS analysis identified key degraded metabolites, including cyclotrisiloxane, hexamethyl; benzene,  1,3-dimethyl; benzene, 1,2,4-trimethyl; and cyclotetrasiloxane, octamethyl. These findings demonstrate that integrating microalgae SW-03 with photosynthetic bacteria in a PMFC presents an effective and eco-friendly strategy for POME treatment.